Nitrogen rate and seed density in irrigated rice: Blast severity, effects on yield and grain protein - Barros, Maykon Rodrigo Gomes de; Viteri , Luis Oswaldo; Oliveira, João Victor de Almeida; Fernandes, Paulo Ricardo de Sena; Mourão, Dalmarcia de Souza Carlos; Rocha, Layane Carmem Arruda da; Rocha, Raimundo Nonato Carvalho; Nardino, Maicon; Santos, Gil Rodrigues dos (Revista de Ciencias Agrícolas, 2025)
Blast is the most important rice disease worldwide, primarily due to the interaction of climatic and the environment factors nitrogen fertilization management, and sowing densities, all of which favor the disease progression and directly affect productivity. Here, we evaluated the effect of nitrogen (N) rates and seed densities (SD) on the Area Under the Disease Progress Curve (AUCPD) of rice blast, caused by the pathogen Pyricularia grisea, in rice grown under flood irrigation during the vegetative and reproductive stages, as well as its influence on grain yield and protein content. The experiment, carried out under field conditions, was organized in a randomized complete block design, in a in a 2 x 5 x 4 factorial scheme, with four replications. The results show that high ND and SD favored an increase in the AUDPC of leaf and panicle blast, between the two rice cultivars (BRS A704 and BRS A706 CL) affecting yield and crude protein (CP) content in the grain. However, ND above 140 kg ha-1 led to an increase in yield and protein content for both cultivars, inserted in an area with blast and red rice infestation.